Constraints and promising interventions to strengthen fish seed systems in Sub-Saharan Africa: Evidence from Ghana - Ragasa, Catherine; Kruijssen, Froukje; Agyakwah, Seth Koranteng; Mensah, Emmanuel Tetteh-Doku; Asmah, Ruby; Ataa-Asantewaa, Martha; Amewu, Sena; Loison, Sarah Alobo (Elsevier, 2026)
CONTEXT Aquaculture has surpassed capture fisheries in terms of production and is among the fastest growing food sectors. It has great potential to contribute to food security and nutrition, poverty reduction, jobs, and environmental sustainability. Fish seed is increasingly considered to be a major driver and disabler of aquaculture development. However, little is known about how fish seed systems operate, their challenges and opportunities, or entry points for strengthening them. OBJECTIVE This study analyzes primary data on the challenges and opportunities faced by various actors along the fish seed chain, documents the lessons from a fish seed project (Ghana Tilapia Seed Project, 2019–2022), and provides an analysis of entry points for strengthening fish seed systems. METHODS Using an analytical framework that tracks germplasm base, seed production and quality, seed availability and distribution, and the information flow along the fish seed value chain, we analyze the case of Ghana, the top producer of farmed tilapia in sub-Saharan Africa. The study uses a mixed-methods approach, including value chain analysis, action-oriented research methods, and statistical analysis of survey data. RESULTS AND CONCLUSIONS Findings indicate that the initial rapid growth in tilapia production in Ghana was partly due to an improved local strain released in 2004; however, the recent stagnation is largely caused by seed-related issues (poor maintenance and improvement of germplasm base, seed quality and availability, lack of information and coordination, and lack of enforcement of regulations). This study highlights the successes and lessons learned from the Ghana Tilapia Seed Project on broodstock distribution, training on fingerling production, establishment of nurseries, and training of fish farmers. The lessons highlight the need for policy changes and capacity building related to strain development and broodstock management. SIGNIFICANCE These findings fill the large gap in evidence on the functioning of fish seed systems and how to strengthen them. They can directly inform ongoing country-level efforts and programs aiming to develop aquaculture.